2005
DOI: 10.1108/13598540510589197
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of e‐procurement in supply chains

Abstract: Optimizing the internal supply chain for direct or production goods was a major element during the implementation of enterprise resource planning systems (ERP) which has taken place since the late 1980s. However, supply chains to the suppliers of indirect materials were not usually included due to low transaction volumes, low product values and low strategic importance of these goods. With the advent of the Internet, systems for streamlining indirect goods supply chains emerged and were adopted by many compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 5 publications
1
116
0
4
Order By: Relevance
“…1 Transaction costs reduction: cost-related benefits have been mentioned by a number of authors (e.g., Croom and Johnston, 2003;Presutti, 2003;Yen and Ng, 2003;Hawking et al, 2004;Puschmann and Alt, 2005;Tatsis et al, 2006;Croom and Brandon-Jones, 2007;McConnell, 2009;Karthik and Kumar, 2013) and include reduced price, administration and inventory costs, and inaccuracies (Smart and Harrison, 2003).…”
Section: P E-p Adoption Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Transaction costs reduction: cost-related benefits have been mentioned by a number of authors (e.g., Croom and Johnston, 2003;Presutti, 2003;Yen and Ng, 2003;Hawking et al, 2004;Puschmann and Alt, 2005;Tatsis et al, 2006;Croom and Brandon-Jones, 2007;McConnell, 2009;Karthik and Kumar, 2013) and include reduced price, administration and inventory costs, and inaccuracies (Smart and Harrison, 2003).…”
Section: P E-p Adoption Driversmentioning
confidence: 99%
“…Apart from positive impacts which facilitate Pe-P's adoption, a range of authors (e.g., MacManus, 2002;Zheng et al, 2004;Puschmann and Alt, 2005;Tatsis et al, 2006;McConnell, 2009) has identified a number of general inhibitors, which include:…”
Section: P E-p Adoption Inhibitorsmentioning
confidence: 99%
“…In a study of e-procurement in public sector organisations in the UK, Croom and Brandon-Jones (2007) found that increases in communication between customers and suppliers assisted knowledge sharing. Information provision in areas such as forecasts and inventory management can enable collaboration between buyers and suppliers (Puschmann & Alt, 2005). Similarly, data exchanged on demand or raw materials flow can assist with co-ordination of production for both trading partners (Lancioni et al, 2003).…”
Section: Communicationmentioning
confidence: 99%
“…In order for any digital engagement in business activities, the channel of communication had to be negotiated [27]. With the implementation of enterprise resource planning (ERP) or manufacturing resource planning (MRP) systems in the 1980s electronic data interchange (EDI) connections with suppliers were established [84]. Technology at this point did not provide the open interfaces necessary for flexible business connectivity.…”
Section: From Web Evolution To Development Of Flexible Epmmentioning
confidence: 99%
“…Although connected common messaging formats for encoding business activities are not developed and open communication could not be established [27]. Relationships with business partners were designed in indirect procurement [84]. Indirect procurement focused on products and services for maintenance, repair and operations (MRO) and products and services that are neither part of the end product nor resold directly [111].…”
Section: From Web Evolution To Development Of Flexible Epmmentioning
confidence: 99%